The future of the European power market - Fabio Genoese; Christian Egenhofer; Michael Hogan; Christian Redl; Markus Steigenberger; Patrick Graichen; Graham Weale (Intereconomics, 2015)
The European power market is undergoing signifi cant changes. The EU has set an ambitious goal of reducing its greenhouse gas emissions by 40 per cent by 2030. This will require significant investment in renewable energy sources such as wind and photovoltaics as well as measured policies to deal with the fl uctuating capacity offered by these renewables. The integration of national power systems into a single European system would provide huge benefi ts in smoothing such fluctuations, enabling the EU power market to further increase its reliance on renewables. Current power generators and government regulators will inevitably face challenges adapting to the new market environment, but experience from other countries and regions could provide useful guidance.
Keywords: 330; Energiemarkt; Förderung erneuerbarer Energien; Marktstruktur; Angebot; Nachfrage; Europa; Welt